Update to role of the neutrophil lymphocyte ratio in patients with advanced NSCLC undergoing immunotherapy - Richardet, Eduardo; Acosta, Luciana Paola; Magi, Ignacio; tello Alfonso, Rocio; Peruchin, Rita Vanessa; Perea, Pablo; Molina, Matias; Richardet, Martin (Journal of clinical oncology, 2022)
e21041Background: The tumor microenvironment TME is a heterogeneous mixture of different tumor cells, necrotic cells and immune infíltrate.Furthermore nerves and vasculature immersed in the surrounding stroma. The TME cells have different immunological phenotypes. The infiltrating lymphocytes of the tumor stroma (tils) and neutrophil lymphocyte ratio (NLR) are a reflection of the state of "inflammation" in the TME and his systemic repercussion. In our institution we have carried out several research studies studying different markers of inflammation, such as BMI, TILs and NLR in different solid tumors. We conclude that these markers of inflammation have a role in tumor behavior, prognosis and response to treatment. The main objective was investigated the relationship between as NLR and progression-free survival (PFS).in patients with NSCLC who received immunotherapy. The secondary objective was to analyze if there is a relationship between ORR and NLR in patients with NSCLC. Methods: Retrospective and analytical study of patients of Instituto Oncológico de Córdoba. Patients with stage IV NSCLC were analyzed. Were included patient who performed IT alone or in combination with another immunomodulator or platinum-based chemotherapy. The cut-off value for NLR > or < 3 was taken. ORR was evaluated by RECIST criteria. For the statistical analysis of survival, Chi-Square test and Kaplan-Meyer test were used. Results: 52 pts with NSCLC were selected, the average age was 67 years. Of the total number of subjects analyzed, 75% (39) presented non-squamous histology and 25% (13) presented squamous histology. All performed IT (anti PD1) alone or in combination with another immunomodulator (Ipilimumab) or platinum-based CT. Of total patients analized, 27 pts had a NLR < 3; and 25 pts NLR > 3. The median overall survival (OS)was 8.5 months for general population. Patients with an NLR < 3, the median PFS was 14.9 months and those with an NLR > 3 was 5.5 months (p: 0.01). When analyzed the ORR in pts with NLR < 3 it was 21% and those with NLR > 3 the ORR was 4% with statistically significant differences (p:0.02). All patients had follow-up of at least 1 year4 patients (8%)with NLR < 3 had disease progression at 6 months in differencies with patients with NLR > 3 that had progression 13 pts (25%)(p:0.01) and these differences were maintained when we evaluated the PFS at year. Conclusions: Patients with NLR < 3 had better progression-free survival and ORR. It is possible that NLR is a very useful and easily accessible predictive factor in patients with NSCLC undergoing immunotherapy.